Planificación y diseño paisajístico en los ejes viales estructurantes de la ciudad de Neiva como estrategia de mitigación y adaptación al calentamiento global (2021)
Global warming is constantly growing and cities too, therefore, it is necessary to find affordable solutions to mitigate this problem and adapt to it. Accordingly, the maintenance of urban trees is vital for countless benefits, such as the capture of particles harmful to the environment and the climatic comfort granted. In an urbanity, the greatest generation of CO2 occurs on the road, where the incidence of vehicle traffic is high; In this sense, the project is developed in the city of Neiva, specifically on the road route of Avenida 26, this is highlighted by its proximity to the Benito Salas airport, it denotes relevance for its active commerce and frequent traffic. Finally, the purpose is to formulate planning and landscape design strategies, which provide tools for the improvement and incorporation of trees suitable for use in the road separators, regulating temperature and contributing to reduce CO2 emissions.